Human plasmacytoid dentritic cells elicit a Type I Interferon response by sensing DNA via the cGAS‐STING signaling pathway. Issue 7 (27th May 2016) - Bode, Christian; Fox, Mario; Tewary, Poonam; Steinhagen, Almut; Ellerkmann, Richard K.; Klinman, Dennis; Baumgarten, Georg; Hornung, Veit; Steinhagen, Folkert
Abstract : Transfection of DNA or cyclic dinucleotides into the cytosol of human pDCs elicit a type I IFN response independent of TLR9. cGAS and STING are expressed in pDCs and IFN induction in response to DNA or cyclic dinucleotides is dependent on the activation of STING and TBK1 suggesting that human pDC express a functional active cGAS‐STING pathway. Abstract : Plasmacytoid dendritic cells (pDCs) are a major source of type I interferon (IFN) and are important for host defense by sensing microbial DNA via TLR9. pDCs also play a critical role in the pathogenesis of IFN‐driven autoimmune diseases. Yet, this autoimmune reaction is caused by the recognition of self‐DNA and has been linked to TLR9‐independent pathways. Increasing evidence suggests that the cytosolic DNA receptor cyclic GMP‐AMP (cGAMP) synthase (cGAS) is a critical component in the detection of pathogens and contributes to autoimmune diseases. It has been shown that binding of DNA to cGAS results in the synthesis of cGAMP and the subsequent activation of the stimulator of interferon genes (STING) adaptor to induce IFNs. Our results show that the cGAS‐STING pathway is expressed and activated in human pDCs by cytosolic DNA leading to a robust type I IFN response. Direct activation of STING by cyclic dinucleotides including cGAMP also activated pDCs and knockdown of STING abolished this IFN response. These results suggest that pDCs sense cytosolic DNA and cyclic dinucleotides via the cGAS‐STING pathway and that targeting this pathway could be of therapeutic interest.